Rocksalt-Zincblende–Wurtzite Mixed-Phase ZnO Crystals With High Activity as Photocatalysts for Visible-Light-Driven Water Splitting - Li, Titao; Cai, Haihuai; Li, Caifu; Liu, Xiaolong; Huang, Feng (Frontiers in Chemistry, 2020)
Finding out the factors that dominate photocatalytic activity is always an essential topic towards the development of highly active photocatalysts. The increased photoactivity of ZnO:Ga (L) may be attributed to the existence of homojunctions and resultant oxygen vacancies in triphasic ZnO:Ga (L), which can reduce the recombination of photogenerated carriers and provide them higher doping efficiency and higher optical gain. Then, the photocatalytic behaviors of as-prepared N doped crystals have been studied and rationalized to understand the role of each of species played in light absorption and photo activation. The N-doped ZnO:Ga (L) sample which showed higher activity than N-doped ZnO:Ga (B) and ZnO:Ga (L), the high activity could be explained by increase of visible light absorption and presence of empty impurity levels introduced by N doping.